Are the collagen types and density in the wound healed after midline and transverse laparotomy different? An experimental study in mice - Kargın, Süleyman; Doğru, Osman; Küçükosmanoğlu, İlknur (Journal of Surgery and Medicine, 2021)
Background/Aim: Whether midline or transverse incision is superior in laparotomy is still controversial. The aim of this study was to investigate the total collagen amounts in wound healing after midline and transverse incisions and reveal whether there was a difference between these two laparotomy techniques. Methods: Twenty-four BALB/c mice were randomly divided into three groups (control, midline, and transverse groups). Mice were sacrificed 28 days after the surgical procedures. The samples were examined histochemically in terms of total collagen density, Type I and Type III collagen rate and maturation index. Results: Total collagen density, Type I collagen rate and maturation index were slightly insignificantly higher and Type III collagen rate was insignificantly lower in the transverse incision group compared to the midline group (P=0.486, P=0.541, P=0.336 and P=0.541, respectively). Conclusion: The total collagen density, Tip I and Tip III collagen amounts, and maturation index of wounds healed after transverse and midline laparotomy are similar according to this experimental model.